Identification of clones that encode chicken tropomyosin by direct immunological screening of a cDNA expression library. - Helfman, D M (1983)
A cDNA library of approximately equal to 9,000 members has been prepared from chicken smooth muscle mRNA by using the plasmid expression vector pUC8. Addition of Sal I and EcoRI linkers at different stages during the preparation of the cDNA resulted in a population of molecules, most of which had EcoRI linkers at the end of the cDNA that corresponded to the 5' end of the template mRNA and Sal I linkers at the end that corresponded to the 3' end of the mRNA. The cDNA molecules then were inserted into a EcoRI-Sal I-cut plasmid vector, pUC8, that contains the transcriptional and translational start sequences from the lacZ gene upstream of the EcoRI site. The sequential addition of the linkers to the cDNA ensured that most of the cDNAs were inserted into pUC8 in the proper orientation for expression. The colonies were replica plated onto nitrocellulose filters and lysed in situ with chloroform vapor. The library was screened for colonies producing products immunologically related to chicken tropomyosin by incubating the filters first with a rabbit antitropomyosin antibody and second with a 125I-labeled goat anti-rabbit IgG. Two colonies were detected that reacted specifically with the antisera. Plasmids from both clones have been partially subjected to sequence analysis; both plasmids contain cDNAs that encode tropomyosin. These protocols are potentially useful for the identification of cDNA clones for genes expressed at low levels from large cDNA expression libraries.